MANAJEMEN DAYA TARIK WISATA RELIGI : STUDI KASUS MAKAM PANGERAN JAYAKARTA, JATINEGARA KAUM - Adrian Farsyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Religius tourism is one type of tourism that is commonly found in Indonesia, such as the Tomb of Prince Jayakarta. The historical and religious elements contained in it make this location crowded by pilgrims and visitors. This research aims to explore more about the figure of Prince Jayakarta and the management of religious tourism attraction at the Tomb of Prince Jayakarta, Jatinegara Kaum, Jakarta, with the main focus on optimising the potential of this destination. Using a qualitative descriptive analysis method, the data obtained in this study came from the process of observation, interviews, and documentation, which were then analysed more deeply using written sources with similar topics. The results of this study indicate that the implementation of tourist attraction management at the Tomb of Prince Jayakarta needs to be improved optimally and professionally in order to increase the number of visitors as well as benefits for the local community.